1997
DOI: 10.1080/01496399708003234
|View full text |Cite
|
Sign up to set email alerts
|

New Technetium-99M Generator Technologies Utilizing Polyethylene Glycol-Based Aqueous Biphasic Systems

Abstract: Two new schemes for TcOJMo0~-separations fiom OH-and MOO: -media using polyethylene glycol (PEG)-based aqueous biphasic systems (ASS) have been developed. The two most important salt solutions in current -Tc-generator technologies, OH-and MOO: , also salt out PEG to form ABS. In liquidfliquid PEG-ABS, pertechnetate can be separated from molybdate with separation factors as high as 10,000. Stripping is accomplished by reduction of the TcO; and back extraction into a salt solution. The strip solution can be the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 21 publications
1
36
0
1
Order By: Relevance
“…Therefore, the results reported here exemplify the less favorable energy region for 99m Tc production (24/19 MeV) and can serve as a reasonable worst-case approximation. Polyethylene glycol-based aqueous biphasic extraction chromatography resin was selected for separation because it is known to retain pertechnetate from industrial alkaline waste (14) and was reported for separation of medical 99m Tc (15). A range of other resins of the same nature, namely the Tentagel (Rapp Polymere) and ChemMatrix (PCAS BioMatrix) product lines, were tested recently by others and showed similar results (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the results reported here exemplify the less favorable energy region for 99m Tc production (24/19 MeV) and can serve as a reasonable worst-case approximation. Polyethylene glycol-based aqueous biphasic extraction chromatography resin was selected for separation because it is known to retain pertechnetate from industrial alkaline waste (14) and was reported for separation of medical 99m Tc (15). A range of other resins of the same nature, namely the Tentagel (Rapp Polymere) and ChemMatrix (PCAS BioMatrix) product lines, were tested recently by others and showed similar results (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…4 plots D and D W values for iodide versus increasing concentration of (NH 4 ) 2 SO 4 , K 2 CO 3 , KHCO 3 (ABEC only), and NaOH in PEG-2000 ABS, and onto ABEC-5000. It is interesting to note that the trend for distribution ratios for a chaotropic anion such as pertechnetate increases with increasing |− G hyd | of the salting-out agent, [15,20] does not seem to hold true for iodide with the ABEC resin, i.e., iodide has a lower D W value in the K 2 CO 3 salt system, than in the (NH 4 ) 2 SO 4 system. However, as discussed earlier (Fig.…”
Section: Iodide Partitioning In Abs and Onto Abec From Different Saltmentioning
confidence: 93%
“…We have previously demonstrated this feature with quantitative partitioning of 99 TcO 4 − to the PEG-rich phase of several high ionic strength solutions [3]; a property which we have exploited in the removal of 99 TcO 4 − from simulants of the highly alkaline radioactive waste tanks at the Hanford, WA site [4] and from solutions of MoO 4 2− in caustic found in 99m Tc-generator technologies [15]. In addition, the similarities between TcO 4 − and ReO 4 − , has allowed development of effective separations strategies for ReO 4 − /WO 4 2− and ReO 4 − /MoO 4 2− [16], important separations in radiopharmacy and hydrometallurgy.…”
Section: Liquid/liquid Iodide Species Partitioning Studiesmentioning
confidence: 97%
“…Polyethylene glycol (PEG) based aqueous biphasic systems (ABS) is a greener analytical technique compared to traditional solvent extraction system as both the phases in ABS are aqueous in nature [1]. ABS is formed when watersoluble polymer PEG and polymer like dextran, starch, polyvinyl alcohol, etc., with one another or PEG with certain inorganic salts like Na 2 SO 4 , (NH 4 ) 2 SO 4 , Na 2 HPO 4 , Na 2 CO 3 etc.…”
Section: Introductionmentioning
confidence: 99%